Evaluating the ‘logical framework approach’ towards learning-oriented development evaluation - Gasper, Des (Public Administration and Development, 2000)
The logical framework approach has spread enormously, including increasingly to stages of review and evaluation. Yet it has had little systematic evaluation itself. Survey of available materials indicates several recurrent failings, some less easily countered than others. In particular: focus on achievement of intended effects by intended routes makes logframes a very limiting tool in evaluation; an assumption of consensual project objectives often becomes problematic in public and inter-organizational projects; and automatic choice of an audit form of accountability as the priority in evaluations can be at the expense of evaluation as learning.

Management not models: adaptability, responsiveness, and a few lessons from football - Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approaches to development over the last 30 years, most aid infrastructure continues to concentrate on the design and subsequent implementation of closed models. This article does not propose an alternative to blueprints, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a supplementary management and learning approach which enables implementers to be dynamic, adaptive, and responsive to problems and opportunities. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.

The Use and Abuse of the Logical Framework Approach: A Review of International Development NGOs' Experiences - Bakewell, Oliver; Garbutt, Anne (Sida, 2005)
The logical framework approach (LFA) has come to play a central role in the planning and management of development interventions over the last twenty years. Although the logical framework has become universally known, it is far from universally liked. It has been the subject of much criticism over the years, concerning both the theoretical basis of the approach, and the way it is applied in practice. In this review, we have attempted to take stock of the current views of international development NGOs on the LFA and the ways in which they use it.